FITRAH CONCEPT IN AL-QUR’AN : An Effort of Fitrah Development in Islamic Education - Ahmad Hijazi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2012)
This paper studies on an effort of Islamic education in developing Fithrah. This is based on the fact that to understand a good Islamic education, conceptually it cannot be separated from an understanding toward humans themselves as the agent of education. It is clear that humans are given fithrah to listen, see, and think about surroundings. With this potency, they are hoped to be educated scientifically to conduct research and analyze to get conclusion and think so that they get knowledge and scientific findings.